Inactivation Methods of Trypsin Inhibitor in Legumes: A Review - Aviles-Gaxiola, Sara; Chuck-Hernandez, Cristina; Serna Saldivar, Sergio O (Journal of food science, 2018)
Seed legumes have played a major role as a crop worldwide, being cultivated on about 12% to 15% of Earth's arable land; nevertheless, their use is limited by, among other things, the presence of several antinutritional factors (ANFs ‐ naturally occurring metabolites that the plant produces to protect itself from pest attacks.) Trypsin inhibitors (TIs) are one of the most relevant ANFs because they reduce digestion and absorption of dietary proteins. Several methods have been developed in order to inactivate TIs, and of these, thermal treatments are the most commonly used. They cause loss of nutrients, affect functional properties, and require high amounts of energy. Given the above, new processes have emerged to improve the nutritional quality of legumes while trying to solve the problems caused by the use of thermal treatments. This review examines and discusses the methods developed by researchers to inactivate TI present in legumes and their effects over nutritional and functional properties.